Simple and sensitive detection of triazophos pesticide by using quantum dots nanobeads based on immunoassay. Issue 1 (1st January 2019) - Liao, Yun; Cui, Xueyan; Chen, Ge; Wang, Yuanshang; Qin, Guoxin; Li, Mingjie; Zhang, Xiuyuan; Zhang, Yudan; Zhang, Chan; Du, Pengfei; Yan, Feiyan; El-Aty, A. M. Abd; et al.
ABSTRACT: A rapid, ultra-sensitive and simple fluorescence immunoassay (FLISA) on CdSe/ZnS Quantum dots (QDs) for recognition pesticide triazophos have been established. In this assay, the immunoassay uses (CdSe/ZnS) Quantum dots (QDs) as a probe that carries monoclonal antibody (mAb). The free triazophos and OVA-haptens were competed for binding the mAb on the surface of the QDs. Therefore, the concentration of TRIAZ can get by calculation of the detection of fluorescence value. The assay has a linear response in the 10 ng L −1 –25 μg L −1 TRIAZ concentration range, and limit of detection (IC10 ) was 0.508 ng L −1 . The recovery rate in the case of spiked samples ranges from 82.6% to 96.6%, and the RSD is <20%. FLISA can accurately and sensitively screen out triazophos in representative actual samples that contain trace levels of pesticides, it can play a prominent part in agricultural product and environmental detection.